The restaurant : from concept to operation - Walker, John R., 1944-. (Wiley, 2011)
"Restaurant owners will continue to turn to The Restaurant because it helps them gain the skills needed to master every challenge and succeed in this highly competitive and rewarding industry. Each chapter has been revised, updated, and enhanced with numerous industry examples, sidebars, charts, tables, photographs, and menus. Greater emphasis is placed on restaurant business plans, restaurant management, and restaurant operations. The themes of sustainability and sustainable restaurant management have been added throughout. New sections have also been included on purchasing meat, cocktails, and the early history of eating out. All of this information will help restaurant owners make the decisions necessary to build a thriving business."--